Provincializing global history : money, ideas, and things in the Languedoc, 1680-1830 - Livesey, James (Yale University Press, 2020)
A micro-history of eighteenth-century systemic change that places ordinary French lives alongside global advances. This book explores the eighteenth-century modernization of the coastal province of Languedoc. Mining a wealth of archival sources, James Livesey unveils how provincial elites, peasant households, and local political institutions began to implement such changes as establishing a credit system and building networks of natural historians and agronomical innovators who introduced new plants and farm machinery to the region. These practices were gradually embedded in daily life and gave rise to connections between the province and the broader world.